Bridging the gaps in the global governance of antimicrobial resistance: the UN sustainable development goals and global health security agenda [version 2; peer review: 2 approved] - Soumyo Mukherji; Andrew Hursthouse; Anjali Parasnis; Suparna Mukherji; Fiona Henriquez; Kavita Sachwani; Regina Esiovwa; John Connolly (Routledge Open Research)
Background This paper examines the suitability of extant governance frameworks at an international level for addressing antimicrobial resistance (AMR), which is a creeping crisis for global health security. Methods Our study begins by evaluating the place of antimicrobial resistance (AMR) within United Nations (UN) Sustainable Development Goals (SDG) targets and indicators. This is followed by a discussion of the global health security agenda (GHSA). We examine how AMR needs to be taken more seriously within global policy frameworks based on adopting a One Health approach. The research is supported by a systematic analysis of the national action plans for addressing AMR published by the World Health Organisation (WHO). Results We determine that political leaders need to do more to promote the problem of AMR and that global health institutions need to invest more energy in thinking about how AMR is governed as part of an already busy global health security agenda. This includes building capacities within health systems, embedding evaluation processes, and enhancing public service leadership within this area. Conclusions Our review of global policy frameworks and the national plans for AMR highlight the patchy coverage of AMR strategies globally and nationally. This article represents a springboard for future research including whether and to what extent a One Health approach to AMR in the environment has been implemented in practice within national health and environmental systems.